Analysis of Determinants of Financial Management Behavior as Social Capital of Millennial and Gen Z Women in Bekasi Regency - Apriani, Erna; Latif, Abdul; Permana, Indra (Journal of Business and Behavioural Entrepreneurship, 2024)
The role of women is vital as social capital; women's financial behaviour is an important capital in the future economic journey; women's financial management behaviour will have an impact on the level of children's education and finance, thereby reducing the level of low education in the context of the golden Indonesia 2045. The research objectives are formulated in the following specific objectives: (1) Analyzing the role of financial knowledge on education level and financial management behaviour and financial knowledge on financial management behaviour through the mediation of education level. (2) Analyzing the role of personality traits on education level and financial management behaviour, as well as personality traits on financial management behaviour through the mediation of education level. (3) Analyzing the role of education level on women's financial management behaviour. The data analysis method in this research is associative causality with a quantitative approach. The analysis method uses Structural Equation Modeling (SEM) with SmartPLS software. The sample in the study was the female gender of the millennial generation and Gen Z, who were already working with a focus on the Bekasi district. The research sampling technique used purposive sampling, as many as 100 samples of the female labour force over 15 years of age who work. The results showed that financial knowledge has no effect on financial management behaviour, financial knowledge on education level has no effect, personality traits on financial management behaviour have a positive effect, personality traits on education level has a positive effect, and education level on financial management behaviour has a positive effect. Financial knowledge on financial management behaviour through mediation Education level does not affect financial management behaviour. Personality Traits on financial management behaviour through mediation Level of Education affects financial management behaviour.